2015
DOI: 10.1021/acs.jpcb.5b04408
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Caged Molecule Dynamics to JG β-Relaxation: I

Abstract: The paper (Sibik, J.; Elliott, S. R.; Zeitler, J. A. J. Phys. Chem. Lett. 2014, 5, 1968-1972) used terahertz time-domain spectroscopy (THz-TDS) to study the dynamics of the polyalcohols, glycerol, threitol, xylitol, and sorbitol, at temperatures from below to above the glass transition temperature Tg. On heating the glasses, they observed the dielectric losses, ε″(ν) at ν = 1 THz, increase monotonically with temperature and change dependence at two temperatures, first deep in the glassy state at TTHz = 0.65Tg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 94 publications
8
69
0
Order By: Relevance
“…Terahertz spectroscopy is by far not the only technique that can be used to measure the VDOS. Similar measurements can be obtained by methods such as neutron scattering, light scattering, Brillouin scattering, low-frequency Raman scattering and optical heterodyne detected optical Kerr effect techniques [2]. The advantage of THz-TDS is its simplicity and robustness of use, with minimal practical constraints on performing the experiments in a laboratory setting, straightforward and accurate data extraction and the availability of commercial terahertz spectroscopy systems.…”
Section: Comparison Of Terahertz Spectroscopy To Scattering Techniquesmentioning
confidence: 81%
See 4 more Smart Citations
“…Terahertz spectroscopy is by far not the only technique that can be used to measure the VDOS. Similar measurements can be obtained by methods such as neutron scattering, light scattering, Brillouin scattering, low-frequency Raman scattering and optical heterodyne detected optical Kerr effect techniques [2]. The advantage of THz-TDS is its simplicity and robustness of use, with minimal practical constraints on performing the experiments in a laboratory setting, straightforward and accurate data extraction and the availability of commercial terahertz spectroscopy systems.…”
Section: Comparison Of Terahertz Spectroscopy To Scattering Techniquesmentioning
confidence: 81%
“…A further examination of these results and other high-frequency data on amorphous systems clearly revealed that the vitrification of JG-beta relaxation is a universal process observed across a wide size and chemistry of glass-forming systems, and that the sensitivity of the high-frequency techniques to this effect is linked to the associated changes in the caged dynamics [2,7,8].…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations